Christianity : the first three thousand years - MacCulloch, Diarmaid; MacCulloch, Diarmaid (2010)
We live in a time of tremendous religious awareness, when both believers and non-believers are deeply engaged by questions of religion and tradition. This ambitious book ranges back to the origins of the Hebrew Bible and covers the world, following the three main strands of the Christian faith, to teach modern readers how Jesus' message spread and how the New Testament was formed. We follow the Christian story to all corners of the globe, filling in often neglected accounts of conversions and confrontations in Africa and Asia. And we discover the roots of the faith that galvanized America, charting the rise of the evangelical movement from its origins in Germany and England. We meet monks and crusaders, heretics and saints, slave traders and abolitionists, and discover Christianity's essential role in driving the Enlightenment and the Age of Exploration, and shaping the course of World Wars I and II.--From publisher description
A millennium of beginnings (1000 BCE-100 CD). Greece and Rome (c. 1000 BC-100 CE) ; Israel (c. 1000 BCE-100 CD) -- One Church, one faith, one Lord? (4 BCD-451 CD). A crucified messiah (4 BCE-100 CD) ; Boundaries defined (50 CE-300) ; The Prince : ally or enemy? (100-300) ; The Imperial Church (300-451) -- Vanishing futures : East and South (451-1500). Defying Chalcedon : Asia and Africa (451-622) ; Islam : the great realignment (622-1500) -- The unpredictable rise of Rome (300-1300). The making of Latin Christianity (300-500) ; Latin Christendom : new frontiers (500-1000) ; The West : universal emperor or universal pope? (900-1200) ; A Church for all people? (1100-1300) -- Orthodoxy : the Imperial faith (451-1800). Faith in a new Rome (451-900) ; Orthodoxy : more than an empire (900-1700) ; Russia : the third Rome (900-1800) -- Western Christianity dismembered (1300-1800). Perspectives on the true Church (1300-1517) ; A house divided (1517-1660) ; Rome's renewal (1500-1700) ; A worldwide faith (1500-1800) ; Protestant awakenings (1600-1800) -- God in the dock (1492-present). Enlightenment : ally or enemy? (1492-1815) ; Europe re-enchanted or disenchanted? (1815-1914) ; To make the world Protestant (1700-1914) ; Not peace but a sword (1914-60) ; Culture wars (1960-present)
Originally published as: A history of Christianity : the first three thousand years. London : Allen Lane, 2009
Includes bibliographical references (p. [1017]-1112) and index
Keywords: Church history